2018
DOI: 10.1186/s13071-018-3185-x
|View full text |Cite
|
Sign up to set email alerts
|

Species delimitation based on mtDNA genes suggests the occurrence of new species of Mesocestoides in the Mediterranean region

Abstract: BackgroundThis study is the first contribution to the molecular taxonomy of Mesocestoides spp. from domestic and wild carnivores in the Mediterranean area. A total of 13 adult worms and 13 larval stages of Mesocestoides spp. were collected from domestic and wild carnivore hosts in Italy and Tunisia. Samples collected in the Slovak Republic were used as comparative samples from outside the Mediterranean. The genes cytochrome c oxidase subunit 1 (cox1) and NADH dehydrogenase subunit 1 (nad1) of the mitochondrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Interestingly, all three Mesocestoides sequences derived from adult worms from Eurasian badgers were very similar (Additional file 1: Tables S1-S3) to these four isolates from rodents. In all phylogenetic trees, the four sequences from rodents and all available sequences from badgers formed one phylogenetic group, distant from M. litteratus, other species and a range of recently identified Mesocestoides genotypes from Italy and Tunisia [32,33]. This group of sequences displayed the highest similarity to M. vogae (syn.…”
Section: Molecular Identification Of Mesocestoides Sppmentioning
confidence: 95%
“…Interestingly, all three Mesocestoides sequences derived from adult worms from Eurasian badgers were very similar (Additional file 1: Tables S1-S3) to these four isolates from rodents. In all phylogenetic trees, the four sequences from rodents and all available sequences from badgers formed one phylogenetic group, distant from M. litteratus, other species and a range of recently identified Mesocestoides genotypes from Italy and Tunisia [32,33]. This group of sequences displayed the highest similarity to M. vogae (syn.…”
Section: Molecular Identification Of Mesocestoides Sppmentioning
confidence: 95%
“…3a, b). Recently, Varcasia et al [34] reported a series of findings of larvae of this species from domestic dogs of south Italian, Sicilian and Tunisian origin. In addition to larval isolates, the isolate TUN01 ( cox 1 sequence MH463506), which originated from an intestine of a domestic dog from Tunisia, represented the first and only record of an adult individual that is genetically matched to the individuals examined in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…The sequences with high similarity (but not complete identity) included cox 1 and nad 1 sequences of another series of domestic dogs and cats from south Italy, Sardinia, Sicily and Tunisia [34]; the nad 1 sequence of an isolate from a domestic dog (Hirzmann et al personal communication) (Fig. 2b); and the 12S rDNA sequence of larvae from domestic dogs (GenBank: MH992719 (unpublished) and KP941431 [43]) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations